2015
DOI: 10.1530/eje-15-0313
|View full text |Cite
|
Sign up to set email alerts
|

Clinical applications of cortisol measurements in hair

Abstract: Cortisol measurements in blood, saliva and urine are frequently used to examine the hypothalamus-pituitary-adrenal (HPA) axis in clinical practice and in research. However, cortisol levels are subject to variations due to acute stress, the diurnal rhythm and pulsatile secretion. Cortisol measurements in body fluids are not always a reflection of long-term cortisol exposure. The analysis of cortisol in scalp hair is a relatively novel method to measure cumulative cortisol exposure over months up to years. Over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
142
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(148 citation statements)
references
References 73 publications
(103 reference statements)
2
142
0
4
Order By: Relevance
“…Evidence is accumulating for the potential application of HCC in clinical and epidemiological studies (Wester and van Rossum, 2015;Wosu et al, 2013) and various relationships have been demonstrated between HCC and, for example, Cushing's Syndrome (Manenschijn et al, 2012), cardiovascular disease (Manenschijn et al, 2013), depression and mood disorders (Dettenborn et al, 2012b), and anxiety (Steudte et al, 2011). However, the association between HCC and subjectively measured stress remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence is accumulating for the potential application of HCC in clinical and epidemiological studies (Wester and van Rossum, 2015;Wosu et al, 2013) and various relationships have been demonstrated between HCC and, for example, Cushing's Syndrome (Manenschijn et al, 2012), cardiovascular disease (Manenschijn et al, 2013), depression and mood disorders (Dettenborn et al, 2012b), and anxiety (Steudte et al, 2011). However, the association between HCC and subjectively measured stress remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, the measurement of cortisol and cortisone in scalp hair has emerged as a method to estimate the long-term exposure to glucocorticoid hormones in humans (Gao et al, 2015;Wester and van Rossum, 2015). Increased hair cortisol (HairF) and/or cortisone (HairE) have been linked to psychopathology, physical and psychological stressors, and the cardiovascular risk profile (Wester and van Rossum, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Increased hair cortisol (HairF) and/or cortisone (HairE) have been linked to psychopathology, physical and psychological stressors, and the cardiovascular risk profile (Wester and van Rossum, 2015). Furthermore, they are promising markers in the evaluation of endocrine diseases of the HPA axis (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As such, cortisol (human) or corticosterone (rodents) are promising candidates for biomarker status, as they can be noninvasively collected from urine, saliva, blood, or hair follicles [22,[134][135][136] . Glucocorticoids (GCs), secreted from the adrenals in hourly pulses and after stress with the goal of maintaining resilience and health, display an impressive diversity of actions, mediated by mineralocorticoid and GC receptors [137,138] .…”
Section: Cortisol/corticosteronementioning
confidence: 99%